The Psychological Impact of Covid-19 Pandemic on Medical Undergraduates: A Study from BPKIHS, Dharan (Journal of Psychiatrists' Association of Nepal, 2021)
INTRODUCTION Since the start of the COVID-19 pandemic, the impact that it can have on mental health has been consistently highlighted. Subsequently there have been calls for universities to monitor the mental health of their students considering the unique set of stressors faced by them. This study is an attempt to understand how our students are doing and to plan appropriate psychological interventions to help themMETHODOLOGY Online questionnaires of Depression, Anxiety, Stress Scale (DASS-21) and Impact of Event Scale (IES) were distributed to the students currently pursuing MBBS and BDS in BP Koirala Institute of Health Sciences.RESULT 409 students responded to the questionnaires. The prevalence of depression, anxiety and stress among the respondents were 39.1%, 35.7% and 35.0% respectively. All three were more common in first and second year students and in those with past history of mental illness (p